2017
DOI: 10.1021/acs.jpca.7b00859
|View full text |Cite
|
Sign up to set email alerts
|

Full QM Calculation of RNA Energy Using Electrostatically Embedded Generalized Molecular Fractionation with Conjugate Caps Method

Abstract: In this study, the electrostatically embedded generalized molecular fractionation with conjugate caps (concaps) method (EE-GMFCC) was employed for efficient linear-scaling quantum mechanical (QM) calculation of total energies of RNAs. In the EE-GMFCC approach, the total energy of RNA is calculated by taking a proper combination of the QM energy of each nucleotide-centric fragment with large caps or small caps (termed EE-GMFCC-LC and EE-GMFCC-SC, respectively) deducted by the energies of concaps. The two-body Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
42
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 79 publications
0
42
1
Order By: Relevance
“…The electrostatically embedded generalized molecular fractionation with conjugate caps (EE-GMFCC) method was employed to perform full QM calculations of electric field in KSI. The detailed description of the EE-GMFCC method can be found in our previous works [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ]. The calculations of the electrostatic potential by the EE-GMFCC method are the same as our previous work [ 16 ].…”
Section: Computational Approachesmentioning
confidence: 99%
“…The electrostatically embedded generalized molecular fractionation with conjugate caps (EE-GMFCC) method was employed to perform full QM calculations of electric field in KSI. The detailed description of the EE-GMFCC method can be found in our previous works [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ]. The calculations of the electrostatic potential by the EE-GMFCC method are the same as our previous work [ 16 ].…”
Section: Computational Approachesmentioning
confidence: 99%
“…Our previous studies on proteins and RNAs have demonstrated that the calculated total energy by EE‐GMFCC is not very sensitive to the embedding charge models. Another study by Liu and Herbert also found that the variations of protein total energies using three different embedding charge models, namely, Mulliken ChElPG and NPA charges, are also very small based on their pp‐GMBE (pair–pair approximation to the generalized many‐body expansion) approach.…”
Section: Computational Approachesmentioning
confidence: 99%
“…Theoretical approaches employing molecular mechanical (MM) force fields have achieved great success in describing biomolecular motion and interaction energies, but traditional nonpolarized force fields are lack of quantum mechanical (QM) effects, such as electronic polarization, many‐body QM interactions, charge transfer and so on . Previous studies have demonstrated that the electronic polarization plays a critical role in accurate description of the binding affinities for protein–ligand complexes and other complex systems …”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies, we combined fragment methods with the MD engine and performed AIMD simulations for large molecular systems including protein, RNA, and hydration of metal ions [ 20 , 34 , 35 ]. In this study, a fragment-based AIMD (FB-AIMD) for combustion is developed, and its performance on the calculation of potential energies, atomic forces, and AIMD simulation of methane combustion are systematically investigated.…”
Section: Introductionmentioning
confidence: 99%